Thermal Condition and Losses in Ultra-High-Speed Generators - Flur Ismagilov; Viacheslav Vavilov; Ruslan Karimov; Denis Gusakov (Universitas Ahmad Dahlan, 2017)
In this paper ultra-high-speed generators operated in intermittent periodic and short-term mode were considered. Experimental studies of losses depending on frequencies in the magnetic core of microelectromechanical energy converters made from amorphous steel were made. Dependence of the flux density from the temperature in the air gap of the experimental layout of high-coercivity permanent magnets was obtained. Computer modeling of the magnetic field distribution on the cross section of the stator magnetic core of microelectromechanical energy converters were made in the software package Ansoft Maxwell. Dependence of friction losses of the rotor around the air from the air temperature was obtained. Comparisons of losses and efficiency of microelectromechanical energy converters in a cold state and after 10 minutes of operation without cooling were made.